2019
DOI: 10.1016/j.chemgeo.2018.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Early stage weathering systematics of Pb and Nd isotopes derived from a high-Alpine Holocene lake sediment record

Abstract: Radiogenic Pb and Nd isotopes are well established tools in palaeoceanographic science tracing ambient climate and continental runoff to the oceans down to sub-millennial timescales. Particularly in case of Pb isotopes, a clear climate dependency of continental isotopic runoff on glacial-interglacial transitions has been observed. Pb isotopes were reported to be released incongruently during initial chemical weathering. This incongruent release implies that Pb isotopic runoff compositions differ from the bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…Our Pb isotope measurements were performed on a Thermo Scientific Neptune Plus MC-ICP-MS at GEOMAR, Kiel. Mass bias correction during Pb isotope measurements was done externally using the Tl-doping technique 62,63 spiked by a NIST997 Tl standard solution (Pb:Tl =~4:1). Given that Tl and Pb fractionate slightly differently during ionization 64 , 205 Tl/ 203 Tl were determined on a session-by-session basis so that NBS981 Pb isotope compositions matched published compositions 63,65 (Supplementary Data 1).…”
Section: Discussionmentioning
confidence: 99%
“…Our Pb isotope measurements were performed on a Thermo Scientific Neptune Plus MC-ICP-MS at GEOMAR, Kiel. Mass bias correction during Pb isotope measurements was done externally using the Tl-doping technique 62,63 spiked by a NIST997 Tl standard solution (Pb:Tl =~4:1). Given that Tl and Pb fractionate slightly differently during ionization 64 , 205 Tl/ 203 Tl were determined on a session-by-session basis so that NBS981 Pb isotope compositions matched published compositions 63,65 (Supplementary Data 1).…”
Section: Discussionmentioning
confidence: 99%
“…Boyle et al, 1977), which can be used to help identify the origin of weathered rocks on continents (e.g. von Blanckenburg et al, 2015;Hindshaw et al, 2018;Süfke et al, 2019;Jang et al, 2020). Iron oxides are also ubiquitous weathering products in soils, which can be transported as particulates in rivers prior to deposition as sediments (Bayon et al, 2004;Kraft et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Gutjahr et al () previously raised concerns that anoxic conditions may result in remobilization of Pb. However, a recent study employing this leaching method on anoxic Holocene sediments in an Alpine lake extracted an unperturbed Pb isotope record (Süfke et al, ), suggesting that reliable authigenic Pb isotopic compositions can be extracted from anoxic sediments. Experiments with sediments from a temperate acidic lake have similarly shown that post‐depositional Pb mobility did not occur (Davis & Galloway, ).…”
Section: Resultsmentioning
confidence: 99%
“…NBS997 Tl standard was added aiming for a Pb/Tl ~ 4 (Belshaw et al, ). The most accurate 205 Tl/ 203 Tl ratio required for mass bias correction was determined on a session‐by‐session basis so that the sum of all offsets of all six Pb isotope pairs for NIST NBS 981 equaled 0 ppm compared with published compositions of Baker et al () (see Süfke et al, ). This always led to slightly higher 205 Tl/ 203 Tl than certified for NIST NBS997 because of the slightly different ionization behavior of Tl compared with Pb (Thirlwall, ).…”
Section: Methodsmentioning
confidence: 99%